Bacteriophage Endolysins and their Applications. (June 2016) - Ajuebor, Jude; McAuliffe, Olivia; O'Mahony, Jim; Ross, R. Paul; Hill, Colin; Coffey, Aidan
Endolysins (lysins) are bacteriophage-encoded enzymes that have evolved to degrade specific bonds within the bacterial cell wall. These enzymes represent a novel class of antibacterial agents against infectious pathogens, especially in light of multidrug-resistant bacteria, which have made antibiotic therapy increasingly redundant. Lysins have been used successfully to eliminate/control bacterial pathogens in various anatomical locations in mouse and other animal models. Engineering tactics have also been successfully applied to improve lysin function. This review discusses the structure and function of lysins. It highlights protein-engineering tactics utilised to improve lysin activity. It also reviews the applications of lysins towards food biopreservation, therapeutics, bioifilm elimination and diagnostics.